The potential of role-play in undergraduate psychology training / Marie Caltabiano … [et al.] - Caltabiano, Marie; Errington, Ed; Sorin, Reesa; Nickson, Amanda (Penerbit UiTM (UiTM Press), 2018)
This paper reports on the use of role-play as a scenario-based learning approach in the teaching of counselling skills, client assessment and diagnostic interviewing within psychological training. While role-play is not a new technique in teaching such skills, its use is generally reserved for the training of higher level students. This paper explores the use of role-play for undergraduate training, its usefulness and how ambiguity and uncertainty can be incorporated into scripts for more effective training. Through a process of constructivist learning, students arrive at meaning between each other in how they approach even improvised role scripts.